The Strategy of BMT Kube Sejahtera 007 in the Development of Micro, Small, and Medium Enterprise Financing - Aprilia, Tesya; Suniarti, Gustia (Institut Agama Islam Negeri Parepare, 2024)
This research examines the strategy of Baitul Maal wa Tamwil (BMT) Kube Sejahtera 007 in developing financing for Micro, Small and Medium Enterprises (MSMEs) in Central Bengkulu. MSMEs have a crucial role in the Indonesian economy, but often face challenges in accessing financing. BMT Kube Sejahtera, as a sharia financial institution, is committed to empowering MSMEs through financing products and mentoring programs. The research method used is qualitative descriptive analysis and SWOT analysis. The research results show that BMT Kube Sejahtera has a positive reputation, easy access, and an effective mentoring program in improving the managerial skills of MSME players. However, weaknesses such as limited resources and lack of product diversification were also identified. Opportunities for growth in the MSME sector and the potential for collaboration with other institutions are in the spotlight, while threats come from competition and policy changes. This research recommends the need for innovation in products and increased resources to face future challenges, so that BMT Kube Sejahtera can continue to contribute to the development of MSMEs and local economic growth.